Prevalence of chronic urticaria in children and adults across the globe: Systematic review with meta‐analysis. Issue 2 (11th October 2019) - Fricke, Julia; Ávila, Gabriela; Keller, Theresa; Weller, Karsten; Lau, Susanne; Maurer, Marcus; Zuberbier, Torsten; Keil, Thomas
Abstract: Background and objectives: Urticaria is a frequent skin condition, but reliable prevalence estimates from population studies particularly of the chronic form are scarce. The objective of this study was to systematically evaluate and summarize the prevalence of chronic urticaria by evaluating population‐based studies worldwide. Methods: We performed a systematic search in PUBMED and EMBASE for population‐based studies of cross‐sectional or cohort design and studies based on health insurance/system databases. Risk of bias was assessed using a specific tool for prevalence studies. For meta‐analysis, we used a random effects model. Results: Eighteen studies were included in the systematic evaluation and 11 in the meta‐analysis including data from over 86 000 000 participants. Risk of bias was mainly moderate, whereas the statistical heterogeneity ( I 2 ) between the studies was high. Asian studies combined showed a higher point prevalence of chronic urticaria (1.4%, 95%‐CI 0.5‐2.9) than those from Europe (0.5%, 0.2‐1.0) and Northern American (0.1%, 0.1‐0.1). Women were slightly more affected than men, whereas in children < 15 years we did not find a sex‐specific difference in the prevalence. The four studies that examined time trends indicated an increasing prevalence of chronic urticaria over time. Conclusions: On a global level, the prevalence of chronic urticaria showed considerable regional differences. There is a need to obtain more sex‐specific population‐based and standardized international data particularly for children and adolescents, different chronic urticaria subtypes and potential risk and protective factors. Abstract : We evaluated the prevalence of chronic urticaria worldwide by performing a systematic search in PUBMED and EMBASE. Chronic urticaria seems to be more prevalent in Asia than in Europe and Northern America. Women in Europe and Northern America were more affected by chronic urticaria than men, whereas in children < 15 years we did not find a sex‐specific difference.